2017
DOI: 10.23850/22565035.722
|View full text |Cite
|
Sign up to set email alerts
|

Conservación de uchuva (Physalis peruviana) mediante la aplicación de un recubrimiento a base de quitosano y áloe vera, utilizando el método de aspersión

Abstract: El objetivo de esta investigación fue estimar la vida útil de la uchuva por efecto de la aplicación de un recubrimiento a base de quitosano y áloe vera utilizando el método de aspersión. La Norma Técnica Colombiana (NTC 4580) se empleó para comparar las características físicas de las uchuvas, utilizando como indicadores de deterioro, pérdida de peso, carotenoides totales e índice de color. Las muestras evaluadas se mantuvieron a dos condiciones de almacenamiento; bajo refrigeración (4 °C) y a temperatura ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…López et al (2016) reported a significant weight loss reduction, from 23% to 15%, in cape gooseberry samples stored for 15 days at 17 • C, with the use of a whey and beeswax based coating. Muñoz et al (2017) [38] were able to prolong cape gooseberries stored from 9 to 11 days while maintaining a weight loss of less than 10% with the use of a chitosan and aloe vera based coating. According to what was reported by Pinzón et al (2015), when a samples' losses exceed 10% of the samples' weight, the freshness of the fruits and vegetables disappear.…”
Section: Weight Lossmentioning
confidence: 99%
“…López et al (2016) reported a significant weight loss reduction, from 23% to 15%, in cape gooseberry samples stored for 15 days at 17 • C, with the use of a whey and beeswax based coating. Muñoz et al (2017) [38] were able to prolong cape gooseberries stored from 9 to 11 days while maintaining a weight loss of less than 10% with the use of a chitosan and aloe vera based coating. According to what was reported by Pinzón et al (2015), when a samples' losses exceed 10% of the samples' weight, the freshness of the fruits and vegetables disappear.…”
Section: Weight Lossmentioning
confidence: 99%
“…López et al (2016) reported a significant weight loss reduction from 23% to 15% in cape gooseberry samples stored during 15 days at 17 ºC, with the use of a whey and beeswax-based coating. Muñoz et al (2017) were able to prolong cape gooseberries stored from 9 to 11 days while maintaining a weight loss of less than 10% with the use of a chitosan and aloe vera based coating. According to what was reported by Pinzón et al (2015), when the samples exceed losses greater than 10% of the weight, the freshness of fruits and vegetables disappears.…”
Section: Weight Lossmentioning
confidence: 99%
“…It possesses a high senescence rate, that is, in a few days it is no longer suitable for consumption. Research on conservation is increasing by trying to preserve its properties or studying new alternatives of consumption while, maintaining its sensorial, nutritional, and functional properties (Muñoz-López et al, 2018). Table 4 shows physicochemical and functional properties of Spondia purpurea.…”
Section: Characterizationmentioning
confidence: 99%